Multiple placental surface cysts with intracystic hemorrhaging: A case report and review of the literature. Issue 8 (29th May 2017) - Soyama, Hiroaki; Miyamoto, Morikazu; Sasa, Hidenori; Yoshida, Masashi; Takano, Masashi; Furuya, Kenichi
Abstract: A placental surface cyst is a cystic mass arising from the surface of the placenta. It is seldom complicated by intracystic hemorrhaging and the clinical importance of this kind of case is unclear. Therefore, we present a case of a placental surface cyst with intracystic hemorrhaging. A 29‐year‐old multiparous woman was diagnosed with multiple placental surface cysts with threatened preterm birth and fetal growth restriction on ultrasonography at 26 gestational weeks (GW). At 31 GW, the hemorrhage was identified inside the cyst. At 32 GW, she presented with placental abruption, and emergency cesarean section was performed. Both the mother and her baby survived. Placental surface cysts up to 77 × 65 mm in diameter containing old hemorrhages were discovered, and pathological examination revealed hemosiderin and fibrin deposition. Pregnancy with a placental surface cyst with intracystic hemorrhaging may have the potential for severe obstetric complications.